Gangliocitoma Displásico Cerebelar: Relato de Caso - Mesquita Filho, Paulo Moacir; Susin, Katriane; Köhler, Luiza Rech; Devens, Leticia Bassani; Schwingel, Daniela; Giacomelli, Richard; Manzato, Luciano Bambini; Azambuja Júnior, Nério Dutra (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Lhermitte-Duclos disease (LDD), or cerebellar dysplastic gangliocytoma, is a rare type of cerebellar tumor, from unknown origin. Patients can be asymptomatic for several years, but there are usually imprecise neurological signs for long periods.
Keywords: gangliocitoma; Lhermitte-Duclos; cerebellar tumor; benign tumor